ORGANIC CARBON OF THE SOIL COLONIZED BY AVICENNIA GERMINANS (L) IN THE LOS TOTUMOS SECTOR, MIRANDA, VENEZUELA - Calderon, Rossany Mariet (2025)
The purpose was to quantify the carbon content stored in the soil of the mangrove ecosystem located in the Laguna Grande wetland, Los Totumos sector, Miranda state, Venezuela. The study was developed in three phases: (a) field: which was carried out in May 2019, where 30 surface soil samples were collected. (b) laboratory: the determination of carbon in the soil was carried out, using the potassium dichromate oxidation technique proposed by Walkley and Black (1934), and (c) statistical analysis: during this phase, descriptive means and tests were estimated. Hypothesis testing. From the results obtained, it is evident that there are no significant differences between the plots that were the subject of this investigation, which is possibly due to the coverage conditions of both plots. An estimated total of 32.14 MgCha-1 stored in the wetland soil.